Determination of cobalt and nickel in biological materials using catalytic adsorptive stripping voltammetry - Bobrowski, Andrzej; Zarębski, Jerzy; Królicka, Agnieszka (Univerzita Pardubice, 2012)
The paper discusses the utilisation of the catalytic adsorptive stripping voltammetric method for the simultaneous determination of Co and Ni in biological materials such as hair, oyster tissue, bovine liver and oriental tobacco leaves. For this purpose the most sensitive and selective catalytic-adsorptive system with nioxime and nitrite has been selected. The optimal parameters, including concentration of the supporting electrolyte, pH and accumulation time and potential, have been established. To decompose the sample material microwave digestion with nitric acid has been applied, providing a blank-free approach for the accurate determination of Co and Ni. The elaborated method has been tested on certified reference materials and good agreement between the voltammetric results and the certified values has been obtained.
Keywords: catalytic adsorptive stripping voltammetry; nioxime; nitrite